Mettā in Pāli Literature (Bodhi Path, 2025)
The term "Pāli" refers to a collection of sacred texts used by Buddhists. Theliterature written in the Pāli language primarily addresses religious andphilosophical themes. Pāli literature is comprised of a rich assortment of Buddhisttexts and scriptures. The most significant part of Buddha's teachings is known asthe "Tipitaka," which many believe contains the original teachings of the Buddha.While scholarly opinions vary regarding the existence of writing in India beforethe time of Asoka (3rd century B.C.), there is a consensus among historians thatthe earliest phase of the Buddhist textual tradition was oral. It is believed that boththe Tipitaka and its commentary were written down during the reign ofVattagāmanī Abhaya in the first century B.C. This event took place at the FourthBuddhist Council, where the Pāli Tipitaka was formally recorded for the first time,as it had previously been transmitted orally from generation to generation.Today there is no real peace and happiness in the world. All people are runninghere and there to bring peace and happiness to society. It shows that there issomething lacking in the minds of people. We need the religious principle that canbring peace to individuals and society. Thus, mettā, or ' loving-kindness' becomesan essential factor in restoring peace to society.Different interpretations are made in the case of the word mettā according to thecontext in which it is applicable. Since the word has been arbitrarily used mettāmay denote many meanings. When the concept of love is being discussed, scholarsmay use it differently according to the basic knowledge which they have. Here, thePāli word 'Mettā' is strictly used in the sense of Loving-kindness, and not in thesense of ordinary, sensual, emotional, passionate love. In fact, the word 'Love' hasvarious denotations and connotations in English, according to the contexts inwhich it is used.My research paper shall be focused on mettā in Pāli Literature. Further, I will alsotalk about the Braham vihāra in my research paper.The proposed paper will provide a detailed explanation of these points.
Keywords: Pāli Literature; Mettā; Tipitaka; Peace; Happiness